MORPHOLOGICAL CHANGES IN SOFT PALATINE TISSUES STANDING BEHIND OBSTRUCTIVE SLEEP APNEA SYNDROME: GENERAL PATTERN AND ROLE OF HUMAN PAPILLOMA VIRUS. - Denysenko , Roman; Gychka , Sergiy; Nikolaienko , Sofia; Dikhtiaruk , Oleksandr; Naumenko , Oleksandr (The Ukrainian Scientific Medical Youth Journal, 2021)
snoring and obstructive sleep apnea syndrome (OSAS) are a serious medical problem, as they lead to a complex of complications from various body systems, disrupt the socio-economic sphere and stigmatize patients. To date, a set of treatments has been developed, the most effective of which are conservative therapy using CPAP and surgical interventions - various modifications of uvulopalatopharyngoplasty. However, only a small number of studies have elucidated soft palate tissue pathology in patients with chronic and OSAS. But understanding the morphological changes is one of the key aspects for the development of treatment tactics. The aim of current study is to justify the choice of surgical intervention in the treatment of snoring and OSAS by description of morphological changes of the soft palate and to estimate the impact of HPV infection on the progression of soft palatine remodeling. The study included soft palatine tissue samples, which were removed during surgery for snoring and OSAS in 15 patients. Histological (H&E) and immunohistochemical techniques (Ki-67, p16, Human Papilloma Virus). All patients were divided in two groups according HPV-positivity: 5 persons in HPV-positive group and 10 persons in HPV-negative group. For indicators were estimated: number of cellular layers (CL), number of intraepithelial lymphocytes (per 100 epitheliocytes) (IEL), number of vessels per x100 field (NV), Ki-67 proliferation index (PI). Results shows in HPV+ group: CL - 24,2 (±2,17); IEL - 37,8 (±20,97), NV - 21 (±8,46); PI - 17,6 (±2,51). In HPV- group: CL - 6 (±4,78); IEL - 3,3 (±1,77); NV - 10,7 (±2,67); PI - 7,3 (±2,71). Mann-Whitney criterion shows statistical significant difference between groups for all mentioned indicators. In conclusion: patients with snoring and obstructive sleep apnea syndrome had hypertrophy of the soft palate structures caused by changes in epithelial and connective tissue components. Subepithelial structures underdo the disorganization of connective tissue components with a violation of the histoarchitectonics of collagen fibers, edema and angiomatosis. Thus, the study revealed a number of irreversible pathological processes of soft palate tissues, which is the basis for the choice of surgical treatment tactics including the resection of excess tissue. At the same time HPV-infection leads to more pronounced changes in the epithelial layer and subepithelial tissue with concomitant inflammation that likely to create a negative background for further treatment of OSA syndrome.